The Augmented Reality (AR) Technology Modernized the Evolution of Construction Industry in Malaysia - Mohammad Azlan, Nur Arianna Harissa; Omar, Roshartini; Mohamed, Sulzakimin (Research in Management of Technology and Business, 2022)
The idea of implementation Augmented Reality (AR) is technology applicable when it helps the Architecture, Engineering, and Construction (AEC) industry in visualized their project without actually contact with many people or even need to go to physical sites visit. The globalization of the COVID-19 pandemic, as well as its economic consequences, are expected to wreak havoc on all economies around the world, plunging millions into recession and probably depression. Hence, to counter back the product in the shortest time, AR plays a big role in making it come true. The objectives of this research are to investigate the implementation of Augmented Reality (AR) the technology in the construction industry, to identify the challenges in the implementation of Augmented Reality (AR) technology in the construction industry and to identify the strategies in boosting the implementation of Augmented Reality (AR) technology. As to examine the current condition of AR adaptation technology in Malaysia, an interview session (Qualitative approach) will be held in the AR industry the and AEC industry. Here, semi-structured interviews using Google Meet act as the main tool for collecting data. Consider that higher exposure to Augmented Reality technology will benefit the AEC industries. The findings in this research expose the AEC industry to new technology and aid the industry in dealing with the new norm of the COVID-19 pandemic. It is envisaged that this would enhance their traditional enterprises and bring them in line with IR 4.0.